Contrasting National Plant Protection Needs, Perceptions and Techno-Scientific Capabilities in the Asia-Pacific Region - GC, Yubak D.; Hadi, B. A. R.; Wyckhuys, K. A. G. (Frontiers in Sustainable Food Systems, 2022)
Pests and pathogens inflict considerable losses in global agri-food production and regularly trigger the (indiscriminate) use of synthetic pesticides. In the Asia-Pacific, endemic and invasive organisms compromise crop yields, degrade farm profitability and cause undesirable social-environmental impacts. In this study, we systematically assess the thematic foci, coherence and inclusiveness of plant protection programs of 11 Asia-Pacific countries. Among 23 economically important diseases and 55 pests, survey respondents identified rice blast, rice brown planthopper, citrus greening disease, Tephritid fruit flies and fall armyworm as threats of regional allure. These organisms are thought to lower crop yields by 20-35% and cause management expenditures up to US $2,250 per hectare and year. Though decision-makers are familiar with integrated pest management (IPM), national programs are invariably skewed towards curative pesticide-intensive control. Pesticide reductions up to 50-100% are felt to be feasible and potentially can be attained through full-fledged IPM campaigns and amended policies. To rationalize farmers’ pesticide use, decision criteria (e.g., economic thresholds) wait to be defined for multiple crop x pest systems and (participatory) training needs to be conducted e.g., on (pest, disease) symptom recognition or field-level scouting. Efforts are equally needed to amend stakeholder perceptions on ecologically based measures e.g., biological control. Given that several Asia-Pacific countries possess robust techno-scientific capacities in various IPM domains (e.g., taxonomy, molecular diagnostics, socioeconomics), they can take on an active role in regionally coordinated campaigns. As such, one can reinvigorate IPM and ensure that preventative, non-chemical pest management ultimately becomes the norm instead of the exception throughout the Asia-Pacific.